2013
DOI: 10.4236/health.2013.57a4011
|View full text |Cite
|
Sign up to set email alerts
|

Low utilization of skilled birth attendants in Ngorongoro Conservation Area, Tanzania: A complex reality requiring action

Abstract: Limited integration of contextual factors in maternal care contributes to slow progress towards achieving MDG5 in sub-Sahara Africa. In Ngorongoro, rural Tanzania, the maternal mortality ratio is high with 642 maternal deaths/100,000 live births. Skilled birth attendants (SBAs) assist only 7% of deliveries. This study, undertaken from 2009 to 2011, used Participatory Action Research involving local stakeholders (Maasai women and men, traditional birth attendants (TBAs), hospital staff) to examine reasons for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
5
18
0
Order By: Relevance
“…Consistent with findings of several studies in Ngorongoro district [8,9,20], where Nainokanoka ward is located, project baseline data indicated a much higher rate of women attending 4+ ANC visits (51%) than facility deliveries (2%) at baseline. In the following 15 months since project implementation, both indicators increased (Figure 1) but the gap between them remains proportionally constant.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with findings of several studies in Ngorongoro district [8,9,20], where Nainokanoka ward is located, project baseline data indicated a much higher rate of women attending 4+ ANC visits (51%) than facility deliveries (2%) at baseline. In the following 15 months since project implementation, both indicators increased (Figure 1) but the gap between them remains proportionally constant.…”
supporting
confidence: 86%
“…[7] In northern Tanzania, particularly in rural districts of Arusha region with a high proportion of Maasai pastoralists, operationalizing these objectives has been difficult, most notably the objective of increasing the adoption of facility delivery-a practice which challenges traditional norms around childbirth in these communities. Several studies in Ngorongoro district of Northern Tanzania document the robust preference for home delivery even among women who attend 4+ ANC visits [8,9]. The seeming paradox of high ANC and low facility birth is not unique to pastoralist groups in Tanzania, and is confirmed by studies of similar populations in Zambia [10], Kenya [11], Uganda [12] and Malawi [13].…”
mentioning
confidence: 89%
“…This argument concurs with the findings of Byrneet al,(2016), who observed that MHS provided by TBAs adheres to the traditional practices of their clients, which makes their services more appealing. Other studies concur that the holistic approach of TBAs takes into account the cultural conceptualization of maternal health (Akunga et al, 2014;Kaingu et al, 2011;Roggeveen et al, 2013). Table 1 also reveals that approximately two thirds of the respondents associate post-partum complications with supernatural factors.…”
Section: Resultsmentioning
confidence: 52%
“…[7] In northern Tanzania, particularly in rural districts of Arusha region with a high proportion of Maasai pastoralists, operationalizing these objectives has been difficult, most notably increasing the adoption of facility delivery--a practice which challenges traditional norms around childbirth in these communities. Several studies in Ngorongoro district of Northern Tanzania document the robust preference for home delivery even among women who attend 4+ ANC visits [8,9]. This seeming paradox is not unique to Tanzania, as confirmed by studies in Zambia [10], Kenya [11], Uganda [12] and Malawi [13].…”
mentioning
confidence: 96%
“…Barriers to accessing skilled delivery services in rural Sub-Saharan Africa are well documented and commonly cited factors include: fear of mistreatment or abuse in facilities [14,15], long distance and difficulty in access [9], poverty and education [9], lack of decision-making power and support [16,17], other culture issues such as birth position and preference for traditional birth attendants [13,18], lack of knowledge of risk and promotion of health seeking behavior [19].…”
mentioning
confidence: 99%